2016
DOI: 10.20344/amp.6942
|View full text |Cite
|
Sign up to set email alerts
|

Neuropatia Auditiva: Avaliação Clínica e Abordagem Diagnóstica

Abstract: RESUMOIntrodução: A neuropatia auditiva é uma condição na qual há alteração na condução neuronal do estímulo sonoro. Este trabalho pretende descrever e caracterizar a casuística de doentes com neuropatia auditiva. Material e Métodos:Realizámos um estudo transversal, retrospetivo, com descrição de uma série de casos consecutivos. O diagnóstico da neuropatia auditiva foi definido nas seguintes situações: Presença de otoemissões acústicas com potenciais auditivos de tronco encefálico ausente ou anormal e presença… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2017
2017
2018
2018

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 19 publications
(31 reference statements)
0
1
0
Order By: Relevance
“…ANS is described in the literature as presence of TEOAE and absent or altered BAEP, generating hearing impairment mainly for speech recognition and comprehension (28) . Several studies have shown the locations of hearing lesions that coincide with ANS, such as the tectorial membrane, inner and outer hair cells, impaired synapses between inner hair cells and fibers of spiral ganglion neurons, impaired electrical transmission of fibers of the cochlear nerve, and problems related to myelination of the cochlear nerve (29,30) . Thus, ANS mainly affects the path of hair cells external to the brainstem, which would justify the presence of this type of impairment in this population, considering that MMC isolated or associated with ACMII is characterized by anatomical alteration throughout the CNS (28) .…”
Section: Resultsmentioning
confidence: 99%
“…ANS is described in the literature as presence of TEOAE and absent or altered BAEP, generating hearing impairment mainly for speech recognition and comprehension (28) . Several studies have shown the locations of hearing lesions that coincide with ANS, such as the tectorial membrane, inner and outer hair cells, impaired synapses between inner hair cells and fibers of spiral ganglion neurons, impaired electrical transmission of fibers of the cochlear nerve, and problems related to myelination of the cochlear nerve (29,30) . Thus, ANS mainly affects the path of hair cells external to the brainstem, which would justify the presence of this type of impairment in this population, considering that MMC isolated or associated with ACMII is characterized by anatomical alteration throughout the CNS (28) .…”
Section: Resultsmentioning
confidence: 99%